Implementasi Kurikulum Merdeka pada Mata Pelajaran PJOK di SD Al Madina Wonosobo - Lukluil Badriyah; Ipang Setiawan; Agus Widodo Suripto; Moch Fahmi Abdulaziz (Universitas Negeri Semarang, 2024)
The education curriculum in Indonesia is always changing with the times.. The aim of this research is to find out how to implement the Merdeka Curriculum in Physical education subjects at SD Al Madina Wonosobo. The research method used is descriptive qualitative. Data collection techniques use observation, interviews and documentation. Data analysis techniques use data reduction, data presentation and drawing conclusions. The research results show that the application of Physical education learning consists of 3 activities, first the introduction, then the core and the conclusion. Then there are obstacles, namely educators' lack of training, lack of teacher creativity in modifying learning facilities and infrastructure and mindset. So the efforts made to overcome these obstacles are by attending workshops, increasing the creativity of Physical education teachers and sharing to change mindsets in teaching. The conclusion of this research is that the implementation of the merdeka curriculum in Physical education learning at SD Al Madina Wonosobo has been carried out well. Starting from implementation, obstacles and efforts to overcome these obstacles, everything has gone well.